2022
DOI: 10.1108/pr-05-2021-0320
|View full text |Cite
|
Sign up to set email alerts
|

The influences of cross-cultural adjustment and motivation on self-initiated expatriates' innovative work behavior

Abstract: PurposeDrawing upon the cross-cultural adjustment (CCA) model and self-determination theory, this study investigated the influence of CCA (work, interactional, and general adjustment) and motivation (autonomous and controlled) on the innovative work behavior of self-initiated expatriates (SIEs).Design/methodology/approachMulti-source data were collected from 213 SIEs and their supervisors working in the United Arab Emirates to provide an understanding of the role of SIEs' CCA and motivation and their innovativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Intrinsic motivation does not help students achieve innovative results, which differs from previous studies that concluded that intrinsic motivation is a predictor of innovative behavior and has a significant positive motivational effect on such behavior. [45][46][47] This implies that the transformation of motivation into results requires certain conditions. Intrinsic motivation is a necessary, but not sufficient, condition for innovative achievements, as it also requires students' efforts and implementation, while extrinsic motivation plays a positive role, which is inconsistent with extrinsic motivation affects creativity negatively by reducing intrinsic motivation.…”
Section: Conclusion and Recommendations Theoretical Significancementioning
confidence: 99%
“…Intrinsic motivation does not help students achieve innovative results, which differs from previous studies that concluded that intrinsic motivation is a predictor of innovative behavior and has a significant positive motivational effect on such behavior. [45][46][47] This implies that the transformation of motivation into results requires certain conditions. Intrinsic motivation is a necessary, but not sufficient, condition for innovative achievements, as it also requires students' efforts and implementation, while extrinsic motivation plays a positive role, which is inconsistent with extrinsic motivation affects creativity negatively by reducing intrinsic motivation.…”
Section: Conclusion and Recommendations Theoretical Significancementioning
confidence: 99%
“…Furthermore, this study investigates extrinsic variables, like worldwide employment prospects, cultural disparities, and support from organizations, which influence the development of self-initiative expatriates. By comprehending these aspects, both businesses and individuals can enhance their readiness in addressing the distinctive obstacles and prospects that self-initiative expatriates contribute to the global workforce (Hussain & Zhang, 2023). This section makes a valuable contribution to the overarching conceptual framework for comprehending the development of self-initiative expatriates, by conducting a thorough investigation of the various factors that influence them.…”
Section: Factors Influencing the Evolution Of Self-initiative Expatri...mentioning
confidence: 99%
“…For example, expatriates with more intrinsic or autonomous motivation are more likely to be more creative, enjoy the task and accept challenging situations. Such as being more innovative or successful in cross-cultural adjustment during expatriation (Hussain and Zhang, 2023; Peltokorpi and Jintae Froese, 2009). Third, engagement and persistence in the behavior can be predicted, as intrinsic motivation is generally associated with greater satisfaction.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Expatriate research has focused heavily on expatriate success measured in several approaches; performance (Setti et al ., 2022; Zhao et al ., 2020), adjustment (Schreuders-van den Bergh and Du Plessis, 2016; Wechtler et al ., 2017), innovative behavior (Hussain and Zhang, 2023), retention (Richardson and Wong, 2018) and embeddedness (Chen and Shaffer, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation